“EL LENGUAJE DE SEÑAS Y SU INCIDENCIA EN LA TELEVISION QUEVEDEÑA” - ROBERTO CARLOS VELIZ MACKLIFF (2017)
The present investigation was carried out at the facilities of Radio Rey Televisión, located in the Quevedo Canton, province of Los Ríos, considering the Quevedo deaf-mute association as the population, with the objective of establishing the incidence of sign language in the television of the Quevedo canton, as an information resource in the process of teaching sign language when broadcasting information. Language is known as the ability that human beings acquire to express their knowledge, thoughts and feelings through words, however, there is a large percentage of the population that cannot express their ideas through words, since They have some hearing disability that allows them to carry out this function. For there to be a correct development and much greater inclusion for people with hearing disabilities, it is necessary that from education, both teachers and students have prior knowledge about sign language, which is why, especially teachers, must train and perform basic communication skills in sign language, thus, students who have reduced hearing will have support in the classroom that will give them the opportunity to express their knowledge, thoughts and ideas without feeling excluded. Technology worldwide has always been an important part of society and education, it has evolved by leaps and bounds and has contributed to all the professions in which human beings operate, in a satisfactory way, thanks to technology, the individual has experienced new ways of learning, new knowledge, managing to obtain satisfactory learning, to acquire new habits, attitudes and values that allow living in a fair and advanced society, and thus raise the academic level in the teaching-learning process. through the application of new teaching methods and techniques, so that the subject can enrich their personal and professional training.